A case of orbital dirofilariasis in New York. (2nd November 2017) - Walters, Stephen; Levi, Michael H.; Coyle, Christina M.; Park, Jean; Barmettler, Anne
ABSTRACT: A 39-year-old female presented with a 5-day history of left inferonasal periocular swelling and associated intermittent itching. Ophthalmologic examination demonstrated a 4 × 8 mm subcutaneous painless mass localized anterior to the medial left lower orbital rim. An excision of the mass was performed, and pathology revealed Dirofilaria . The patient improved over the 3 months of postoperative follow-up. Although several human cases of pulmonary dirofilariasis have been reported in the United States, periocular dirofilariasis has been rarely reported in the United States. The case report is in compliance with the Health Insurance Portability and Accountability Act.